Peran Perempuan dalam Perspektif Hadis: Pendekatan Islamisasi Pengetahuan terhadap Ketahanan Keluarga Muslim: Women’s Roles in Hadith: An Islamization of Knowledge Approach to Muslim Family Resilience - Maryam Qonitat (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
This study explores women's roles through the Prophetic traditions (hadith) and examines how the Islamization of knowledge can strengthen contemporary Muslim family resilience. While historical narratives have often confined women to domestic roles, this research argues that authentic hadiths—when interpreted through the Islamization framework—reveal dynamic, multidimensional roles for women: spiritual, intellectual, social, and economic, all within the family structure. By integrating classical Islamic scholarship (turath) with contemporary analysis, the study offers a comprehensive framework for empowering Muslim women and promoting balanced familial roles. Using a qualitative, content analysis approach, the paper examines selected hadiths alongside the works of leading Islamic scholars. It draws on the Islamization concepts of Syed Muhammad Naquib Al-Attas and Ismail Raji Al-Faruqi, presenting a holistic epistemological framework that reinterprets hadiths on women’s contributions to family and society. Rejecting secular narratives, this paradigm embeds divine values to recontextualize women as nurturers, educators, intellectuals, and socio-economic participants within the bounds of Shari’ah. The study concludes that a resilient Muslim family requires a return to an Islamic worldview, where hadiths are understood contextually and applied transformatively. This approach enables the formation of balanced, spiritually grounded family units capable of navigating modern challenges.